Therapeutic rTMS in Neurology Principles, Evidence, and Practice Recommendations - Platz, Thomas (Springer International Publishing : Imprint: Springer, 2016)
This book is a comprehensive reference on therapeutic repetitive transcranial magnetic stimulation (rTMS) that documents the current status in the field. While introductory chapters cover the neurophysiology of rTMS and present imaging information about its mechanisms of action, the main focus of the book is the clinical applications of rTMS that have been tested to date. These include treatment of paresis, aphasia, and visual neglect in stroke patients, therapy for motor impairment in Parkinson's disease, and applications for tinnitus and neuropathic pain. Based on the available clinical evidence (RCTs, meta-analyses, and systematic reviews), combined with the personal experience of experts in the field, a clinically oriented best evidence synthesis is provided for each therapeutic application, together with a clear description of rTMS algorithms that generate clinical benefits in the target domain. Clinicians and researchers are thereby informed about the state of the art in terms of both the evidence base for therapeutic rTMS and practical issues in its application. A further feature is the presentation of a theoretical model of therapeutic action for each therapeutic target, and a concluding chapter describes a general concept of therapeutic applications of rTMS in neurology and associated fields. Therapeutic rTMS in Neurology will be invaluable for clinicians and researchers in neurology and related fields, inc luding neurologists, physiatrists, and ENT and pain specialists.